Highly reactive electrogenerated zinc: preparation and its use in cross-coupling reactions - Abdul Jalil, Aishah; Triwahyono, Sugeng; Kurono, Nobuhito; Takasugi, Shingo; Tokuda, Masao (The Institution of Engineers, Malaysia, 2005)
Highly reactive zinc metal was prepared by electrolysis of a N, N-dimethylformamide (DMF) solution containing naphthalene and a supporting electrolyte in a one-compartment cell fitted with a platinum cathode and a zinc anode. This highly reactive electrogenerated zinc (EGZn/Naph) was used for transformation of bromoalkanes into the corresponding organozinc bromides, which cannot be achieved by the use of usual zinc metals. Reaction of the organozinc compounds were thus prepared with various aryl iodides in the presence of 5 mol% of palladium catalyst to give the corresponding cross-coupling products in high yields. Arylzinc iodides were also prepared by the use of this highly reactive zinc, and they were reacted with other iodides to give the corresponding cross-coupled biaryls in good yields.